(untitled) (Research, Society and Development, 2022)
Introduction: To compare results of video-assisted thoracic surgical approach (VATS) and of open thoracotomy in performing lobectomy and pneumonectomy regarding hospital stay, chest drainage time, morbidity and mortality. Methods: An observational retrospective study of 149 patients undergoing lobectomy and pneumonectomy for open thoracotomy or VATS from January 2018 to December 2022. Patient characteristics were compared using Student’s t-test, χ2 Pearson and Fisher’s exact test. We performed the Propensity score matching model of analysis for data fitting. Complications were assessed by multivariate logistic regression model for age, sex, lung function, histology, comorbidities and smoking factors. We used Kaplan-Meier estimator and Cox regression to assess hospital stay and thoracic drainage. Results: We performed 130 open thoracotomy and lobectomy by VATS 19. The propensity score model excluded 111 patients in the thoracotomy group. The patients in the VATS group had lower thoracic drainage time (p= 0.011; HR= 0.40; IC95% 0.19 to 0.84) and hospital stay (p= 0.001; HR= 0.23; IC95% 0,10 to 0,54) in the Cox regression model. Multivariate logistic regression for complications as a dependent variable showed VATS with a reduction factor (p = 0.02; OR = 0.13; CI 0.023 to 0.730). There were no significant differences in the characteristics, postoperative complications and mortality between the groups (p = 0.31). Conclusion: VATS is associated with decreased hospital stay, less chest drainage time and less post-operative complications.